Berberine hydrochloride counteracts enhanced IL-8 expression induced by SN 38 in AGS cells. Issue 8 (3rd August 2018) - Chen, Jin; Ma, De-Ning; Fang, Yuan; Zhang, Ning; Zhou, Jia-Min; Yin, Xiao-Lan; Liu, Feng; Chai, Zong-Tao
Abstract: IL-8 over-expression could enhance cancer metastasis. In present study, berberine hydrochloride (BER) triggered proliferative inhibition and G2/M arrest in AGS cells, down-regulated protein expression of cyclin B1, Bcl-2, up-regulated expression of p21, p53 and cleaved caspase 3, but showed no effect on protein expression of CHOP, Bip, and caspase 4. BER could down-regulate the enhanced IL-8 expression through down-regulating ERK1/2 and p38 MAPK over-activation induced by SN 38. The increased IL-8 mediated adhesive ability of AGS cells to HUVECs induced by SN 38, could be reduced by BER. Thus, BER could reduce the side-effect of SN 38 in clinic. Abstract :